UPAYA PENGENALAN EDITORIAL DAN PENULISAN JURNAL ILMIAH PADA TENAGA PENDIDIK DI SMP NEGERI 2 KAMPAR KIRI HILIR KABUPATEN KAMPAR - Fatkhurahman, Fatkhurahman; Hadiyati, Hadiyati (Komunitas Manajemen Kompetitif, 2023)
Abstract: Partner situation analysis, teachers become professional educators, especially for those who have received teacher certification. Teachers are required to write scientific articles published in scientific journals so that their work can be read by various groups in need. Partner problems, teachers are still not familiar with scientific editors in the context of publishing scientific manuscripts, there is still a lack of teacher knowledge about how to submit scientific manuscripts to scientific journal editorials to be published in scientific journals. Submitting scientific manuscripts is the first step for teachers in order to publish their scientific work during teaching. So far, teachers still do not understand what scientific journals are and also how to submit scientific manuscripts to editors so that they can be published in scientific journals. The target output to be achieved in this activity is a form of change in the knowledge and ability of teachers as educators to submit scientific manuscripts to editors to be able to publish their scientific manuscripts to scientific journals. The solution provided in this activity is to provide training on submitting scientific manuscripts to editorial to be published in scientific journals. Based on the results of the service that was carried out on December 15, 2016, information was obtained that there was a change in teacher knowledge about what scientific journal publishers are, the usefulness of publishers, submitting manuscripts to publishers and how strategies for writing articles so that they can be published in scientific journals.